Spreadsheet to Calculate the Economic Feasibility of Anaerobic Manure Digesters on Florida Dairy Farms - Albert de Vries; Russ G. Giesy; Ann C. Wilkie; Roger A. Nordstedt (EDIS)
AN176, a 2-page fact sheet by Albert de Vries, Russ G. Giesy, Ann C. Wilkie, Roger A. Nordstedt, describes a spreadsheet that evaluates the economic feasibility of investment in anaerobic manure digesters on Florida dairy farms that use hydraulic flushing systems for manure management. Includes a link to the spreadsheet and references. Published by the UF Animal Sciences Department, September 2006.